Formulating Questions is the ‘Answer’ for both Learning and Discovery: Probing a New Model for Education - Martins, Vanessa; Logan, Robert K. (New Explorations)

(untitled) (New Explorations Association, 2023)
We describe the importance of exploration and formulating questions to be explored ratherthan studying the answers of the past as a way to reform education based on ideas first formulated byMarshall McLuhan.